An Efficient Analysis of Cloud-based Energy Management System for Secure Data Transmission - Rajassekharan, Dinesh; Murugan, Abbylashnny A/P A (Journal of Electrical Engineering and Automation, 2024)
The traditional method of manual electricity meter reading has limitations, including human errors, inefficiency, and resource intensity. This research proposes a Smart GSM-Based Automated Power Meter Reader System to streamline power consumption monitoring. The system utilizes a GSM module integrated with a digital energy meter to provide real-time, remote power consumption data to utility providers and consumers. This approach reduces manual intervention, enhances accuracy, and promotes energy management. Finally, a user-friendly interface is developed to visualize real-time energy statistics through interactive graphs and tables, enabling users to track consumption trends and make informed decisions.